Effects of Ionic Liquids on Biofilm Formation in a Loop-Type Laboratory Biofilm Reactor. (25th October 2017) - Kanematsu, Hideyuki; Saito, Tatsuki; Barry, Dana M.; Hirai, Nobumitsu; Kogo, Takeshi; Ogawa, Akiko; Tsunashima, Katsuhiko
Abstract : Biofilm formation was carried out using low concentrations of ionic liquid (IL) to investigate the potential control of biofilm formation with IL. A 2000ml reservoir was filled with tap water with/without a low concentration of ionic liquid in aqueous solution. The apparatus (Laboratory Biofilm Reactor: LBR) was a loop type Laboratory Biofilm Reactor (LBR) composed of an acrylic pump and a bottom tank. A pump circulated the water in the loop system of the laboratory biofilm reactor (LBR). The glass specimens were immersed in the LBR with/without a low concentration of ionic liquid in aqueous solution for 2 or 7days. They were observed and evaluated by using Crystal Violet, a 3D optical microscope and a Raman spectrometer to determine their biofilm behavior. The results were discussed from the viewpoint of a cooling pipe system simulation. We found out and confirmed that the formation of biofilm was controlled when a low concentration of aqueous solution of ionic liquids was circulated.